2022
DOI: 10.5267/j.uscm.2021.9.005
|View full text |Cite
|
Sign up to set email alerts
|

The effect of supply chain finance on supply chain risk, supply chain risk resilience, and performance of Vietnam SMEs in global supply chain

Abstract: The purpose of the article is to examine the response of small and medium enterprises (SMEs) in Vietnam to supply chain finance and then have a strategy to use supply chain risk resilience to control supply chain risk and improve supply chain effectiveness and SMEs performance. The analysis results are based on three months of data collected from 890 SMEs in Vietnam. The results show that supply chain finance has a statistically significant positive impact on supply chain effectiveness, SMEs performance and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…A research by Chirambo (2017) showed how microfinance promoted climate change resilience in Africa. Nguyen et al (2022) found that finance strengthened the risk resilience in Vietnam SMEs. Yuan and Li (2022) also disclosed that finance encouraged business resilience in Chinese firms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A research by Chirambo (2017) showed how microfinance promoted climate change resilience in Africa. Nguyen et al (2022) found that finance strengthened the risk resilience in Vietnam SMEs. Yuan and Li (2022) also disclosed that finance encouraged business resilience in Chinese firms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results indicate that credit quality, supply chain integration, information exchange, etc., have a significant effect on the performance of SCFs and SMEs. The response of small and medium enterprises in Vietnam to SCF has been measured by Nguyen et al (2022). According to the results, the SCF has a considerable positive influence on supply chain effectiveness, SME performance and supply chain risk resilience.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Though there was only minor growth in 2019, with 3 papers, 2020–21 saw a significant breakthrough in this subject, with 34 papers out of total 46. In the beginning of year 2022, 3 publications by Nguyen et al. (2022), Wilujeng et al.…”
Section: Descriptive Analysismentioning
confidence: 99%
“…Though there was only minor growth in 2019, with 3 papers, 2020-21 saw a significant breakthrough in this subject, with 34 papers out of total 46. In the beginning of year 2022, 3 publications by Nguyen et al (2022), Wilujeng et al (2022) and Hossain et al (2022) appeared in the literature, representing a good start in this field. From 2012 to 2022, Figure 2 shows the overall number of publications every year.…”
Section: Timelines and Major Publication Outlets Of Studiesmentioning
confidence: 99%